2002
DOI: 10.1038/sj.bjc.6600027
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA breaks and apoptosis in crosslink-hypersensitive V79 cells by the cytostatic drug β-D-glucosyl-ifosfamide mustard

Abstract: To study molecular aspects of cytotoxicity of the anticancer drug b-D-glucose-ifosfamide mustard we investigated the potential of the agent to induce apoptosis and DNA breakage. Since b-D-glucose-ifosfamide mustard generates DNA interstrand crosslinks, we used as an in vitro model system a pair of isogenic Chinese hamster V79 cells differing in their sensitivity to crosslinking agents. CL-V5B cells are dramatically more sensitive (30-fold based on D 10 values) to the cytotoxic effects of b-D-glucose-ifosfamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The present results confirm the important role of caspase-3 in the apoptotic cascade leading to IFOinduced cell death and showed that IFO treatment induces brain cell apoptosis by increasing expression level of caspase-3 and decreasing Bcl-2. Also, the present findings run in parallel with studies by (Schwartz and Waxman, 2001;Becker et al, 2002 andRzeski et al, 2004); they found that caspase-9 plays an essential role in the apoptotic cascade leading to caspase-mediated cell deaths contribute to the neurotoxicity of anticancer drugs in vitro in neuronal cultures and in vivo in the developing rat brain. Under this condition, IFO can activate Bax and Bak leading to cytochrome c release from mitochondria and subsequent caspase activity.…”
Section: Discussionsupporting
confidence: 78%
“…The present results confirm the important role of caspase-3 in the apoptotic cascade leading to IFOinduced cell death and showed that IFO treatment induces brain cell apoptosis by increasing expression level of caspase-3 and decreasing Bcl-2. Also, the present findings run in parallel with studies by (Schwartz and Waxman, 2001;Becker et al, 2002 andRzeski et al, 2004); they found that caspase-9 plays an essential role in the apoptotic cascade leading to caspase-mediated cell deaths contribute to the neurotoxicity of anticancer drugs in vitro in neuronal cultures and in vivo in the developing rat brain. Under this condition, IFO can activate Bax and Bak leading to cytochrome c release from mitochondria and subsequent caspase activity.…”
Section: Discussionsupporting
confidence: 78%
“…The Bcl-2 decline was also involved in apoptosis in DNA repair-deficient rodent fibroblasts treated with UV light (Dunkern et al, 2001b), cisplatin (Dunkern et al, 2001a), glufosfamide (Becker et al, 2002) and methyl methanesulfonate (Ochs et al, 2002). As shown here, contrary to fibroblasts, the Bcl-2 level remained constant upon MNNG treatment in lymphocytes, irrespective of the proliferation state.…”
Section: Discussionmentioning
confidence: 99%
“…These active compounds can react with phosphate, amino, and hydroxyl groups of the bases of nucleic acids. The ultimate alkylating mustards from the oxazaphosphorines are the predominant metabolites that cause DNA damage such as adducts and crosslinks, and DNA strand breaks (SEKER et al 2000;BECKER et al 2002;ZHANG et al 2005b). It is known that DNA damage can trigger programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The oxazaphosphorines are accepted to be DNA damaging agents. A better understanding of the action of these alkylating agents on DNA molecules of cancer cells is important for their optional use in chemotherapy (SEKER et al 2000;BECKER et al 2002).…”
mentioning
confidence: 99%